A deep learning approach to predict crypto-currency price by evaluating sentiment and stock market correlations - Maliha, Miftahul Zannat; Trisha, Ananya Subhra; Tamzid Khan, Abu Mauze; Das, Prasoon; Shakil, Shuhanur Rahman (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.